Tanggungjawab Ilmuan Sosial Dalam Memposisikan Peran dan Permasalahan Budaya Lokal Untuk Penguatan Etika Pluralisme Bangsa - Touwe, Sem (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2020)
This research aims to explain the responsibility of social scientists and their role in addressing issues related to the values of togetherness in cultural, ethnic, racial, and religious diversity, often referred to as multiculturalism. In Indonesia, multiculturalism is sometimes seen as a blessing but also, in narrow perspectives, as a calamity and a cause of destruction. However, multiculturalism in Indonesia as a product of local culture existed long before the formation of the Indonesian state. The data and information in this paper are derived from a desk review of various research reports, book studies, documents, and the author's own experiences conducting relevant research. The core issue discussed in this paper is how to ensure that local culture's multicultural products continue to serve as a guide for the communities that support them in Indonesia. Social scientists must be called upon by their social obligations as analysts and providers of information through their research findings and as spokespersons or prototypes of good behavior, morals, and actions within society. Furthermore, the paper highlights the role of social scientists as leaders of multiculturalism who are objective, open, and courageous in expressing truthful ideas, as truth functions not only as a way of thinking but also as a way of life. The conclusion of this paper indicates that a significant majority of social scientists in Indonesia consciously take responsibility for their academic contributions, which society can utilize, particularly in relation to multiculturalism in Indonesia.